Municipal Bankruptcy and Local Court Funding: What We Can Learn from the City of Detroit, Michigan. (2nd April 2016) - Hartmus, Diane M.; Walters, Julie
Abstract: With a federal bankruptcy judge's grant of chapter 9 protection to the City of Detroit, Michigan, in December 2013, came questions regarding the bankruptcy's implication for myriad stakeholders. Though media attention focused primarily on bondholders, labor unions, and pensioners, one stakeholder received comparatively little attention—the 36th District Court. Located in Detroit, the Court, one of the nation's largest and busiest, is funded via a model requiring local government responsibility for sizable contributions to local courts. As this type of funding model is not unique to Michigan, we analyze key issues presented by the Detroit case in the context of the funding model, and implications not only for it but for other states using similar models, both in terms of court administration and larger issues inherent in federal forms of government such as separation of powers and inherent powers.